UPAYA PELESTARIAN KUDA LUMPING DI KELURAHAN UJUNG GURUN KECAMATAN PADANG BARAT KOTA PADANG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
Kuda Lumping is a traditional art form with complex cultural values, including aesthetic, social, and spiritual values ​​in community life. However, its existence faces the threat of declining appreciation due to the phenomenon of modernization and lifestyle changes, especially among the younger generation. This study aims to describe the form of Kuda Lumping in Ujung Gurun Village and its preservation efforts by the local community through coaching, organizing performances, institutional support, and integration into local cultural activities. The research method used is descriptive qualitative through observation, in-depth interviews, and documentation. The results found that Kuda Lumping preservation is actively carried out through various strategies but still faces challenges such as minimal interest from the younger generation, limited facilities, and the lack of use of digital media for promotion. Therefore, cross-sector collaboration and innovative strategies are needed to strengthen preservation.